Efficiency of fertilizers while cultivation of the winter durum wheat variety “Agat Donskoy" in the southern part of the Rostov region - A. V. Alabushev; A. S. Popov; G. V. Ovsyannikova; A. A. Sukharev; N. E. Samofalova; N. S. Kravchenko (Зерновое хозяйство России)
Over the years of research, the winter durum wheat variety “Agat Donskoy” sown in weedfree fallow showed a good resistance to lodging with no fertilizing (4 points), average resistance to lodging (3 points) with two nitrogen dosings: in spring in thawed frozen soil (N30) and in the period of earing (N30). The winter durum wheat variety “Agat Donskoy” sown after sunflower showed a high tolerance to lodging (5 points) for 3 years on average. Sown in weedfree fallow the largest productivity (6.09 and 6.13 t/ha) and the surplus to the control (0.54 and 0.57 t/ha) were formed by the variety when fertilizing with the basic dosing (P60K40) and with one or two nitrogen dosings (N30 in spring in thawed frozen soil and in the period of earing). At the same time, the grain had a high percentage of protein 15% and gluten 28.1% that corresponded to the 1st quality class. The winter durum wheat variety “Agat Donskoy” sown in weedfree fallow proved to be highly profitable (at the level of 163-201%). The winter durum wheat variety “Agat Donskoy” sown after sunflower produced the largest surplus of yield (1.00 and 1.25 t/ha) when fertilizing with N40P60K40 and the use of one or two nitrogen dosings (N30 in spring in thawed frozen soil and in the period of earing). The profitability of the variety sown after sunflower was 113-147%. According to the GOST the obtained characteristics allow referring the winter durum wheat variety “Agat Donskoy” to the 2-3d quality class.